2011
DOI: 10.1039/c1jm13423j
|View full text |Cite
|
Sign up to set email alerts
|

Nanopores array of ordered mesoporous carbons determine Pt's activity towards alcohol electrooxidation

Abstract: A nanopores array in ordered mesoporous materials matters significantly to the reactant molecules arriving at the active catalytic sites in the interior of the nanostructure. However, how this effect works in the case of electrocatalysis needs investigating. We present that the nanopores array of carbon supports plays a significant role in determining Pt's accessibility and electroactivity. The ordered mesoporous carbons with interconnected pore channels (CMK-3) provide Pt nanoparticles with more than one orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
4
21
0
Order By: Relevance
“…29 The broadness of the peak appeared for C–O bonds owing to the presence of both C=O and C–OH as reported previously. 29…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…29 The broadness of the peak appeared for C–O bonds owing to the presence of both C=O and C–OH as reported previously. 29…”
Section: Resultssupporting
confidence: 76%
“…The highly active porous surface area of OMC along with the homogeneous dispersion of AuNPs provide a faster mass-transfer route which increases the electroactivity of isopropanol despite having higher molecular mass and low polarity. 39…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 10, it can be observed that the TG curves of these two catalysts is almost the same, carbon and light H2O in the catalyst is almost completely removed when the heating temperature in air gets to 500 °C, and the proportion of the re-maining Pt is very close to the theoretical loading of 20 wt% [40,41].…”
Section: Properties Comparison Between the 20-(1/22)-140-2 Pt/c And Tmentioning
confidence: 69%
“…The characteristics are typical to multi-component alloys [7,27,32,36,37]. Normally, the electrochemically active surface area (ECSA) can be obtained from the equation ECSAPt (m 2 /g) = QH/(2.1 × mPt) by integrating the hydrogen ad/desorption charge and using the value of 2.1 C m −2 for the oxidation of a monolayer of hydrogen on a polycrystalline Pt electrode [35,38] Figure 3b, the specific activity of the np-PtRuCuW is 1.8 mA cm −2 , which is 3.6 and 2.9 times that of the PtC and PtRu catalysts (0.5 and 0.63 mA cm ). It can be seen that the peak potentials are comparable for all catalysts while the ratio of the forward anodic peak current density (If) to the reverse anodic peak current density (Ib) is different.…”
Section: Catalytic Activity Of Np-ptrucuw At Anodementioning
confidence: 99%